The Paraventricular Nucleus of the Hypothalamus: Development, Function, and Human Diseases - Qin, Cheng; Li, Jiaheng; Tang, Ke (Endocrinology (Philadelphia), 2018)
The paraventricular nucleus of the hypothalamus (PVH), located in the ventral diencephalon adjacent to the third ventricle, is a highly conserved brain region present in species from zebrafish to humans. The PVH is composed of three main types of neurons, magnocellular, parvocellular, and long-projecting neurons, which play imperative roles in the regulation of energy balance and various endocrinological activities. In this review, we focus mainly on recent findings about the early development of the hypothalamus and the PVH, the functions of the PVH in the modulation of energy homeostasis and in the hypothalamus-pituitary system, and human diseases associated with the PVH, such as obesity, short stature, hypertension, and diabetes insipidus. Thus, the investigations of the PVH will benefit not only understanding of the development of the central nervous system but also the etiology of and therapy for human diseases.